The path of anthelmintic control face to the new CAP 2020-2027 - Dos Santos, Maria José Palma Lampreia (2021)
The European Parliament following the Treaty of Lisbon finally approve the new Common Agricultural Policy (CAP) based on the proposed Multiannual Financial Framework (MFF) for the period 2021-2027. Therefore, the final negotiations can now be started with the Council of the European Union (EU) to reach a final understanding new CAP. The present CAP agreements until reached reinforce the main principle of subsidiarity among the Member States (MS) of European Union (EU) and, on the other hand, they reducing the main general CAP policies and MFF 2021-2027 due the Brexit and correspondent reducing of expenses to financing the European budget. In addition, in line with the new MFF architecture for a more flexible and agile financing framework, food chain measures will be integrated in other budget priorities such as research, innovation and digital policies (Horizon Europe, Digital Europe). Those instruments, as well as, the European Social Fund Plus (ESF+), will also cover health-related actions, such as measures against antimicrobial resistance, in the context of the 'One Health' approach. Moreover, food safety, animal welfare, fight against food waste or sustainable use of pesticides are part of the new Common Agricultural Policy objectives. Nowadays the antihelminth control due the resistance phenomena require an increase in costs to fight this problem among the MS, due the resistance phenomena. The main aim of the paper is analyzing the main challenges of combat the antihelminth due the restrictions of European budget. The methodology is based on a systematic literature review. The main results outline confirms the need of increasing research and strong network efficiency as occurs with COMBAR.